2014
DOI: 10.7182/pit2014432
|View full text |Cite
|
Sign up to set email alerts
|

Lung Transplant or Bust: Patients' Recommendations for Ideal Lung Transplant Education

Abstract: Peer reviewed eScholarship.orgPowered by the California Digital Library University of California A lthough current demand outpaces the supply, patients with end-stage lung disease who are able to get lung transplants can have up to a 75% lower risk of death and significantly better quality of life than patients who stay on the waiting list. [1][2][3] More than 100 transplant centers across the United States ensure that the approximately 1700 patients waiting for a lung transplant (based on Organ Procurement an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 36 publications
0
13
0
Order By: Relevance
“…As in other reports, the value of information repetition and having a support person to assist with retention was suggested. 12,15 Confusion regarding the waitlist testing and worry about remaining listed were also expressed. A recent systematic review and thematic synthesis on patient attitudes on the kidney transplant waitlist describes similar frustrations and identified the burden of tests as 1 of the 6 major themes in this population.…”
Section: Discussionmentioning
confidence: 99%
“…As in other reports, the value of information repetition and having a support person to assist with retention was suggested. 12,15 Confusion regarding the waitlist testing and worry about remaining listed were also expressed. A recent systematic review and thematic synthesis on patient attitudes on the kidney transplant waitlist describes similar frustrations and identified the burden of tests as 1 of the 6 major themes in this population.…”
Section: Discussionmentioning
confidence: 99%
“…• Patients report gaps in understanding the range of treatment options and associated risks and benefits, [164][165][166] as well as required self-care responsibilities after cardiothoracic transplantation/MCS implantation. 164,165,[167][168][169][170] • Understanding and decision-making about transplantation and/or MCS implantation can be driven more by attitudes and emotional factors (fears, expectations, and hopes) than by a systematic weighing of risks and benefits. 167,[171][172][173] • Patients may feel substantial decisional conflict (i.e., uncertainty about how to choose or what choice to make 174 ) when faced with transplantation, MCS, or other medical options.…”
Section: Knowledge and Understanding Of Current Illnessmentioning
confidence: 99%
“…Evidence. [164][165][166][167][168][169][170][171][172][173][174][175][176][177][178][179][180][181] When faced with possible cardiothoracic transplantation and/or MCS implantation, patients' knowledge of their options and responsibilities for self-care is often incomplete. Even with complete knowledge and understanding, attitudes and emotional factors can cloud decision-making about treatment options, and feelings of decisional conflict (i.e., uncertainty about how to choose between options) are common.…”
Section: Knowledge and Understanding Of Current Treatment Optionsmentioning
confidence: 99%
“…It has been shown that the majority of adult lung transplant patients are willing to use Internet resources. 26 Apart from immediate access to peer support, the healthcare organizations can offer secure meeting platforms with personal logins for patients and NoK. In addition to providing a platform for patients to learn more about the illness and receive support, healthcare professionals can use social media to collect data for studies and thus improve the care.…”
Section: Interpretation In Light Of Existing Literaturementioning
confidence: 99%